(3GdeSJTGQ aj GdVQjHI GdYGeI Ydi GdeHjYGJ (B/s - (3GdVehQ, bGSe YHO GdMejOs ((3YeGf(B: s (3OGQ hGFd ddfTQ h GdJhRjY(B, s, 2005)
(3Gdecda HGdVQjHI GdYGeI Ydi GdeHjYGJ h cPG GdhYGA GdVQjHj GVGaI Gdi GdJSLjd aj THcI GdVQjHI GdYGeI Ydi GdeHjYGJ h GdGbQGQ GdVQjHj h GdVQjHI GdeSJMbI(B, (3cPdc NUe GdVQjHI h QOgG h GdeWGdHGJ GdVQjHjI h GdGYJQGV YdjgG(B, (3LQGFe GdJgQH GdVQjHj h GdYbhHGJ h GdJHdjZ GdbGfhfj h CMcGeg h aj GdGNjQ JfGhd JMUjd GdVQjHI hGdJfajP Ydi GdeOjfjf HgG h eSGFd h CMcGe YGeI(B.s
Keywords: (3GdeHjYGJ(B- (3VQGFHs; (3VQGFHs; (3eHjYGJs